2017
DOI: 10.1590/abd1806-4841.20174485
|View full text |Cite
|
Sign up to set email alerts
|

Morbihan disease: a therapeutic challenge

Abstract: Morbihan disease is a rare condition characterized by chronic and persistent erythematous solid edema localized on the face. It is believed to be a complication of rosacea and may occur at any stage of the disease. Features of this condition include variable therapeutic response and great refractoriness. We report a case of a 61-year-old man with rosacea history diagnosed with Morbihan disease, who showed excellent therapeutic response with the combination of deflazacort and oral isotretinoin but developed rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
0
15
0
3
Order By: Relevance
“…Immunohistochemical studies showed D2-40 expression in the lymphatic endothelial cells, which was reported to be the typical phenotype of endothelial cells in Morbihan syndrome[ 7 ]. In addition, CD68 could also act as a histological marker for Morbihan syndrome to exclude carcinoma[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies showed D2-40 expression in the lymphatic endothelial cells, which was reported to be the typical phenotype of endothelial cells in Morbihan syndrome[ 7 ]. In addition, CD68 could also act as a histological marker for Morbihan syndrome to exclude carcinoma[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Choroba Morbihan (Morbihan disease) jest jednostką o niejasnej etiopatogenezie, najczęściej klasyfikowaną jako odmiana lub późne stadium trądziku różowatego [1,2]. Charakteryzuje się spoistym, rumieniowym, najczęściej symetrycznym obrzękiem górnej i środkowej części twarzy.…”
Section: Wprowadzenieunclassified
“…Dermatology Review/Przegląd Dermatologiczny 2020/6 introduction Morbihan disease is a condition of unclear aetiopathogenesis, most often classified as a variety or late stage of rosacea [1,2]. It is characterised by a coherent, erythematous, usually symmetrical swelling of the upper and middle part of the face.…”
mentioning
confidence: 99%
“…Morbihan syndrome, first reported in 1957 by Robert Degos, is a rare entity predominantly affecting Caucasian adults of both sexes in the third and fourth decade of life 1 2. The pathogenesis of the syndrome is not well elucidated 1…”
Section: Introductionmentioning
confidence: 99%